Repeated Optical Biometry Failure as an Underrecognized Marker of Late In-the-Bag Intraocular Lens Decentration in Axial Myopia: A Case Report - Angel Lim; Ni Made Dwipayani (HM Publisher, 2026)
Background: Late in-the-bag intraocular lens (IOL) dislocation is a delayed complication of cataract surgery driven by progressive zonular weakness, with axial myopia recognized as an independent risk factor. Its role as a hidden cause of optical biometry failure, however, has received little emphasis in the literature. Case presentation: A 58-year-old woman with longstanding axial myopia presented seven years after uneventful right-eye phacoemulsification with progressively blurred vision, monocular diplopia, and ghost images. Best-corrected visual acuity (BCVA) was 6/38 in the right eye improving to 6/15 with pinhole; refractometry revealed a new −4.00 D cylinder at axis 90° with persistent visual distortion consistent with irregular astigmatism. Slit-lamp examination showed inferior decentration of an in-the-bag posterior chamber IOL with a visible inferior haptic. Posterior segment evaluation through the displaced optic was hazy. Repeated optical biometry of the affected eye failed to acquire a valid axial-length signal across three sessions, whereas the fellow eye yielded reliable measurements. The patient was referred to a tertiary vitreoretinal center for IOL repositioning or exchange with possible pars plana vitrectomy and scleral fixation. Conclusion: In a myopic pseudophakic eye presenting with new-onset monocular diplopia and an astigmatic shift, repeated failure of optical biometry should be recognized as a critical diagnostic clue to underlying IOL instability, prompting timely tertiary referral and individualized surgical planning.